A Study on Working Women Customer Expectations on Retail Apparel Store Merchandising - T, Sana Ashraf.; Savitha, V. (International Journal of Membrane Science and Technology, 2023)
A well-designed and expertly kept retail environment can draw in more customers, keep them interested, and ultimately result in a more fulfilling shopping experience, raising the likelihood of repeat business and patronage. It takes time and effort to merchandise a store effectively. Evaluation of strategy efficacy frequently, follows market trends, and adjusts to shifting consumer preferences. By doing this, it make shopping enjoyable for customers, entice them to buy again, and ultimately increase sales and brand loyalty. The influence of store merchandising and customer expectations on the success of a retail store is a crucial aspect of retail management and marketing. Visual merchandising is a potent technique that companies use to draw customers in, make their shopping experience memorable, and ultimately encourage impulsive or unexpected purchases. This research study explains the working women customer expectations on store merchandising with respect to store exterior and store interior.